2010
DOI: 10.1523/jneurosci.3947-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

IL-6- and NGF-Induced Rapid Control of Protein Synthesis and Nociceptive Plasticity via Convergent Signaling to the eIF4F Complex

Abstract: Despite the emergence of translational control pathways as mediators of nociceptive sensitization, effector molecules and mechanisms responsible for modulating activity in these pathways in pain conditions are largely unknown. We demonstrate that two major algogens, the cytokine interleukin 6 (IL-6) and the neurotrophin nerve growth factor (NGF), which are intimately linked to nociceptive plasticity across preclinical models and human pain conditions, signal primarily through two distinct pathways to enhance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
240
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(261 citation statements)
references
References 59 publications
15
240
0
Order By: Relevance
“…However, correlations do exist between IL-6 signaling and pain processing, even in the absence of soluble IL-6R. It has been reported that IL-6 and NGF have synergistic effects on nociceptive plasticity (Cafferty et al, 2004;Melemedjian et al, 2010). It is therefore possible that NGF promotes expression of IL-6R in TrkA-expressing neurons, and long-term primary culture could also induce IL-6R expression in nociceptors (von Banchet et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, correlations do exist between IL-6 signaling and pain processing, even in the absence of soluble IL-6R. It has been reported that IL-6 and NGF have synergistic effects on nociceptive plasticity (Cafferty et al, 2004;Melemedjian et al, 2010). It is therefore possible that NGF promotes expression of IL-6R in TrkA-expressing neurons, and long-term primary culture could also induce IL-6R expression in nociceptors (von Banchet et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…At the level of signaling pathways in peripheral nociceptors, recent studies have shown that mammalian target of rapamycin-(mTOR-) and ERK-dependent pathways play a critical role in chronic pain (10)(11)(12)(13)(14). Models of hyperalgesic priming have been developed as a tool to study the transition to chronic pain (10,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…This has been particularly evident in growing axons, both for developing and regenerating axons, but there are several publications supporting the notion that mRNAs and ribosomes are present in mature axons of neurons in the peripheral nervous system (PNS) prior to injury (Ben-Yaakov et al, 2012;Hanz et al, 2003;Koenig et al, 2000;Perlson et al, 2005;Yudin et al, 2008;Zelená, 1970). Studies of cutaneous nerve terminals also suggest that translation of mRNAs can be triggered by pain invoking stimuli (Jimenez-Diaz et al, 2008;Melemedjian et al, 2010). In developing axons, translation of new proteins is needed for response to some guidance cues (Jung et al, 2011).…”
Section: Introductionmentioning
confidence: 99%